LOGWARE : APLIKASI MANAJEMEN PERGUDANGAN SUKU CADANG KAPAL BERBASIS WEB FITUR PELACAKAN BARANG - Adnan, Reza Febriansyah; Hamidin, Dini; Rahmatuloh, Marwanto (Yayasan Nuraini Ibrahim Mandiri, 2024)
This research addresses inefficiencies in warehousing management at Xyz caused by a non-integrated manual system. To overcome this, a web-based warehousing management system was developed using prototype methodology, which allows for incremental development based on user needs. The system was built with CodeIgniter 4 and MySQL, which was chosen for its reliability and flexibility. The implementation results showed significant improvements in operational efficiency, especially in stock tracking, which became faster and more accurate. As a result, the company managed to reduce high operational costs due to previous inefficiencies and improve overall productivity. Recommendations include further integration of the new warehousing management system with existing logistics and purchasing systems, as well as the development of predictive features for inventory optimization based on historical trend analysis and demand forecasting. This study confirms the important role of technology adoption in improving warehousing management and overall company performance.